The determinants of China's ODI to Southeast Asian countries: Further evidence from count data model - Mengjiao Wang (2018)
© Published under licence by IOP Publishing Ltd. This paper investigates the main determinants of China's Outward Direct Investment activities in 11 Southeast Asian countries by using the count data models. Several hypotheses are developed according to literature survey and empirically tested using the count data of the number of China's ODI enterprises in Southeast Asian countries from 2003 to 2015. The results show that China's ODI is determined by the market characteristics of host countries. Chinese investment enterprises are attracted to countries with great market potential, high openness degree and complete infrastructures whereas the natural resources availability and labour cost of host countries have significant negative impact on China's ODI. Except for the characteristics of host countries, Chinese investment enterprises also attach importance to the surrounding market potential of host countries. Moreover, China's ODI and export to Southeast Asian countries are considered to be substitute to each other.